Ramazan musıkisi - Önder, Halil İ. (My University, 2010)
Ramazan, İslam dünyasında olduğu gibi Türkiye’de de coşkuyla karşılanan, hüzünle uğurlanan mübarek bir aydır. Bu mübarek ayın her yönü araştırılmaya değer olup bu ayda icra edilen musıki de bu konulardan biridir. Sadece maddi âlemde değil manevi âlemde ve ona açılan kapı mahiyetindeki ibadet hayatında da estetiğe önem veren Osmanlı, Ramazan-ı Şerife has bir ibadet olan teravih namazlarını aralarda farklı makamlardan ilahiler okuyarak kılma geleneğini oluşturmuş ve bu gelenek günümüze kadar gelmiştir. Ayrıca Ramazan’ın Kuran ayı olması sebebiyle mukabele okuma geleneği de çok önemsenmiş ve Kuran’ın ilahi hitabı ile musıki nağmeleri birleşince ortaya eşsiz bir ahenk çıkmıştır. Eski Ramazanlarda uygulanıp bugün unutulan minarelerden sahur vaktinde temcid okuma geleneği de Ramazan Musıkisi’nin akislerindendir. Bu çalışmayla ramazan musıkisine dair unutulmaya yüz tutan geleneklerimiz hatırlatılmaya ve unutulup gitmemesi için kayıt altına alınmaya çalışılmıştır. Ramazan, Music, Religion music, Teravih, Temcid, Enderun, İlahi, ritüel RAMADHAN MUSIC Ramadhan is a holy month which is welcomed, like in entire Islamic World, with great excitement and fairwelled with sorrow as well in Turkey. All aspects of this holy month is worth to search for. Traditional religious Ottoman music called Musiki which is performed in this month is one of these aspects. Not only in the material world but also in moral and spritual world, the Ottomans gave weight to the importance of aesthatic in the worshipping world, which is the gate to spritual world. They established a tradition of singing spritual songs between the breaks of the ramadhan prayers in different reciting tones which is performed only in Holy Ramadhan and this tradition endured till today. Besides that, because the month of ramadhan is a month of Qur'an, reciting Qur'an reciporically (muqabele) is also valued very much and when divine speach is combined with musical melodies, a wondorous unique harmony comes out. Although it was practiced in old ramadhans today it is forgotton the tradition of reciting ''Temcid'' from minarets at the time of Sahoor (which is last time of eating and drinking before starting fasting). This old tradition is also one of the reflections of the Ramadhan music. With this study our traditions about the Ramadhan music which are about to be forgotton are pushed to be remembered and to avoid annihilation they are tried to be saved. Ramadhan, music, religious music, tarawih, temcid, endaron, divine, ritual
Keywords: İslam Dini_Müzik; Musıki; Müzik